My E-Mosque system: an Islamic android companion - Fauzan, Abdul Rahman Ali; Zeki, Akram M. (Design for Scientific Renaissance, 2014)
This paper describes the documentation for the system development of an android application, My E-Mosque. This mobile application will include different type of functions such as Qiblat direction, Prayer Time, D'zikir, Al-Quran, NFC silent mode and daily du’a. This paper explains about the system development and its entire process by describing the problem, its comparison with the existing mobile application and the difference between the existing mobile applications.